DIPLOMASI PUBLIK INDONESIA DALAM MENINGKATKAN JUMLAH KUNJUNGAN WISATAWAN MANCANEGARA ASAL SINGAPURA MELALUI WONDERFUL INDONESIA PERIODE 2016-2019 - Sherina Amellia (2022)
This study describes Indonesia's public diplomacy efforts in increasing the number of foreign tourist visits to Singapore through Wonderful Indonesia during the 2016-2019 period. Singapore is the main spender of Indonesian tourism, but in 2015-2016 the number of foreign tourist arrivals from Singapore decreased. Therefore, this research raises a research question "How is Indonesian Public Diplomacy in Increasing the Number of Foreign Tourist Visits from Singapore Through the Wonderful Indonesia Program Throughout 2016-2019?". To answer this question, the author uses the theory of diplomacy, the concept of public diplomacy, and the concept of nation branding. Indonesian public diplomacy involves state and non-state actors who work hand in hand in promoting Indonesian tourism through Wonderful Indonesia in Singapore. The results show that the public diplomacy efforts of Indonesian state actors, assisted by non-state actors through the promotion of Wonderful Indonesia, have been proven to increase the number of visits by foreign tourists to Singapore. In addition, the promotions carried out have also increased the country's foreign exchange and given awards to actors. All of these activities aim to spread Indonesian culture and build relationships with the Singaporean public to create a positive tourism image and increase the number of Singaporean tourist visits. However, this promotional activity still has several obstacles to continue promoting its products because the condition of Indonesia's infrastructure around tourist destinations is still inadequate, Indonesia's security level is still lacking, and the promotion budget is small.